Is transcendental healing of painful memories possible? a reflection on the role of pastoral counseling and storytelling - Joseph Okeke; Felix FOkoye (International Journal of Humanities and Innovation (IJHI), 2022)
This study examines the contributions of pastoral counseling and storytelling in healing and restoring painful memories. The study applies Louw's life story and Lartey's relationship-oriented models as the theoretical framework. The data were collected through participant observation, document analysis, and the researchers' long years of experience in pastoral ministry and counseling. The finding reveals that storytelling remains a powerful tool for healing wounded memories. The pastoral counseling and storytelling create a safe space for seekers to interact, find the emotional strength to reignite healing processes, reclaim their volition, and create retrospection that reconnects the healing seekers with their painful memories. The study recommends that government should prioritize memory healing programs, partner with the Church, chiefs, and relevant organizations through sponsorship, provide counseling centers for hurting men to voice out and seek healing in their communities, regulate churches, and reduce violence shown on the South African media in the name of telling our stories or entertainment.